Transitioning from Practice to Health Care Administration: The Later Years - Opelka, Frank G. (Clinics in Colon and Rectal Surgery, 2019)
Since the late 1800s, the role of the physician has evolved substantially beyond mainstream clinical medicine. As fee for service models expanded in the 1980s, resulting in an unsustainable financial crisis in health care, senior physicians stepped up to provide essential input and expertise to administrators on a national level. This model of physician–administrator has evolved to include dual-degree physicians who are equipped with specialized knowledge even at the outset of their career. As physicians are now vital members of health care administration, many will feel the need to transition from clinical practice to a new position where they can effect change on a larger scale. This article will provide insight into such transitions and dual-career pathways and discuss important considerations when faced with this juncture in one's career.
Keywords: health care policy; dual degrees; transition from practice; MBA